The ex hex : a novel - Sterling, Erin (Avon romance., 2021)
"Nine years ago, Vivienne Jones nursed her broken heart like any young witch would: vodka, weepy music...and a curse on the horrible boyfriend..[She] isn't worried it will cause him anything more than a bad hair day or two...until Rhys Penhallow...returns to Graves Glen, Georgia...Vivi realizes her silly little Ex Hex may not have been so harmless after all...Vivi and Rhys have to ignore their off the charts chemistry to work together to save the town and find a way to break the break-up curse before it's too late"--